Depression during multiple sclerosis relapse: relation to disability and relapse severity - Selma Šabanagić-Hajrić; Enra Suljić; Gorana Sulejmanpašić-Arslanagić (Medicinski glasnik, 2016)
Aim: To examine the presence of depressive symptoms in patients with multiple sclerosis relapse and its relation to disability and relapse severity. Methods: This study included 120 patients who were assessed during the acute relapse of multiple sclerosis according to Mc Donald criteria. Depression was assessed using Beck Depression Inventory II (BDI-II) calculating both affective and somatic symptom scores. The Expanded Disability Status Scale (EDSS) measured disability. Relapse severity was graded according to the difference between the EDSS score during relapse and EDSS score before the onset of the attack as mild, moderate or severe. Results: There was statistically significant difference between patients with different level of depression considering age (p<0.001), disability (p<0.001), relapse severity (p=0.005) and disease duration (p=0.032). Significant moderate positive correlation of depression with age (rho=0.43) and disability (rho=0.46) was confirmed. There was moderate correlation between disability and somatic symptoms of depression (rho=0.54, p<0.001) with only weak correlation between disability and affective symptoms of depression (rho=0.31, p<0.01). Multiple regression analysis showed that patient’s age and relapse severity (p<0.05) were independently related to depression in these patients while disability did not. Conclusion: Correlation between disability and depression was mostly due to somatic symptoms of depression. Although highly correlated, depression during multiple sclerosis relapse was not independently predicted by disability. Depression should be recognized and treated independently from disability treatment, especially in the group of older patients with more severe relapse.
Keywords: multiple sclerosis; disability; somatic symptoms; affective symptoms